Considerations regarding the team cohesion impact on handball performance - Macovei, S.; Tonita, F.; Alexandrescu, N.; Popescu, L. (Annals of Ovidius University Constanta-Series Physical Education and Sport/Science, movement and health, 2012)
Introduction. From the perspective of our paper, we consider that creating an optimum cohesion in the handbal team can have favorable influences on performances. Purpose. The present study describes the theoretical premises related to the concept of "cohesion" within the handball team. Content. The cohesion influence on the group productivity has been intensely studied. High cohesion groups can easily establish performance standards and offer a wider range of awards to its members. M.E. Shaw (1981) discovered that highly cohesive groups are cooperative, friendly and they use a democratic form for the behavior control. In low cohesion groups, members are hostile and aggressive, they are pleased when their colleagues make mistakes and they adopt a decision-making autocratic style. Conclusions. Relationships among teammates are decisive to ensure the group cohesion and the efficiency of a team activity depends on the quality of these relationships.